2021
DOI: 10.1002/mdc3.13168
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Progression of Rapid Eye Movement Behavior Disorder in Early Parkinson's Disease

Abstract: BackgroundBackground: Rapid eye movement (REM) sleep behavior disorder (RBD) is associated with neurodegenerative diseases; however, few longitudinal studies assess the individual evolution of RBD and REM sleep without atonia (RWA) in Parkinson's disease (PD). Objectives Objectives: We aimed to evaluate RBD and RWA changes over time as well as potentially influential factors. Methods Methods: RBD and RWA were analyzed using video-supported polysomnography (vPSG) in initially de novo PD patients at baseline and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…There is high correlation of PSG-proven RBD with the RBD questionnaire results, although with variability 30 33 . Since PSG is often performed only once, the RBD questionnaire may be more sensitive to detect RBD, particularly for question 6, which assesses REM sleep behaviors, though is less specific 34 , 35 . Most studies have defined these subjects with subjective dream-enactment behavior without PSG confirmation of REM atonia as having probable RBD (pRBD), and we will use the term pRBD to be consistent with the literature.…”
Section: Methodsmentioning
confidence: 99%
“…There is high correlation of PSG-proven RBD with the RBD questionnaire results, although with variability 30 33 . Since PSG is often performed only once, the RBD questionnaire may be more sensitive to detect RBD, particularly for question 6, which assesses REM sleep behaviors, though is less specific 34 , 35 . Most studies have defined these subjects with subjective dream-enactment behavior without PSG confirmation of REM atonia as having probable RBD (pRBD), and we will use the term pRBD to be consistent with the literature.…”
Section: Methodsmentioning
confidence: 99%
“…Studies that have estimated the prevalence of RBD and/or RSWA in PD have shown that a large proportion of people with Parkinson's disease, including those with more advanced disease, do not have RBD or RSWA. [1][2][3][4][5][6][7][8] Accordingly, we speculate that the majority of individuals in our PD-RSWA group will not develop RSWA or RBD, but motor and cognitive impairment will continue to progress along with decreasing FA. This hypothesis implies that the alterations in corticofugal and corticocortical white matter FA observed in this study impact motor and cognitive function, but not the REM sleep atonia circuitry.…”
Section: Discussionmentioning
confidence: 99%
“…In people with Parkinson's disease, muscle activity during REM sleep is often abnormally elevated (termed REM sleep without atonia, RSWA) and when observed in conjunction with dream enactment (complex movements or vocalizations) reflects the co-expression of REM Sleep Behavior Disorder (RBD). [1][2][3][4][5][6][7][8] Isolated RBD is recognized as a prodromal stage of overt synucleinopathy with approximately 75% of individuals eventually phenoconverting to Parkinson's disease, dementia with Lewy Bodies, or multiple system atrophy within 12 years. 9 While isolated RBD is estimated to be present in about 1% of the population, 10 approximately 30-50% of individuals with Parkinson's disease meet clinical criteria for diagnosis of RBD based on polysomnography-derived evidence of RSWA and dream enactment behavior.…”
Section: Introductionmentioning
confidence: 99%
“…These earlier studies in PD which have not studied RBD with the vPSG have since been superseded by studies utilizing vPSG at multiple time points and have conclusively demonstrated that RBD, which is characterized by REM sleep without atonia (RSWA), is a persistent and progressive feature in RBD. Using vPSG, the DeNoPa study group showed that the RBD prevalence had increased from 25% at baseline to 43% at 2-year follow-up [ 30 ••] and to 52% at 6-year follow-up [ 28 ]. RSWA was independently associated with disease duration and age but not other disease-related factors, suggesting that RSWA could be a progression marker.…”
Section: Rem Sleep Behavior Disordermentioning
confidence: 99%
“…The authors have also introduced the concept of REM behavioral events (RBE), where REM-associated minor motor behaviors and/or vocalizations were seen but the RSWA were below cut-off values. In their series, 31 subjects identified to have RBE at baseline developed full-blown RBD within 6 years [ 28 ]: 38% of RBE positive PD subjects converted to RBD, and 18% of PD subjects with normal REM sleep at baseline converted to RBD over 2 years [ 30 ••]. The prevalence of RBE had also increased over time from 50% at baseline to 63% 2 years later [ 30 ••].…”
Section: Rem Sleep Behavior Disordermentioning
confidence: 99%